Pendekatan Antropologi sebagai Sarana Moderasi Beragama di UIN K. H. Abdurrahman Wahid: Studi Kasus pada Mahasiswa beda Agama di Kampus - Agus Riyadi; Nanda Kartika Putri; Fatimah Arifatul Khair (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: In a diverse academic environment, particularly in religious universities, the importance of fostering religious moderation is increasingly crucial. Religious tolerance among students of different faiths plays a vital role in maintaining peace and harmony on campus. Objective: This study aims to examine the application of religious moderation (tolerance) among students at UIN K. H. Abdurrahman Wahid Pekalongan and to explore the role of anthropology in promoting this moderation within the campus environment. Method: The research employs a qualitative approach and was conducted in 2024 at UIN K. H. Abdurrahman Wahid Pekalongan. Data were collected through interviews, observation, and documentation. Data analysis involved three stages: data reduction, data presentation, and conclusion drawing. Result: The findings reveal that the application of religious moderation among students is well-implemented. It serves as a strategic approach to maintaining harmony among students of different religious backgrounds and fosters peaceful, tolerant, and respectful interfaith interactions on campus. Conclusion: Religious moderation is effectively upheld through an anthropological lens within the university setting, contributing to a culture of mutual respect and coexistence among students of diverse faiths. Contribution: This research provides valuable insights into the relevance of an anthropological approach in strengthening religious moderation among students and offers a scientific reference for further studies in religious and cultural diversity in higher education.